A four step synthesis of violaceic acid. Issue 12 (22nd March 2018) - Cameron, Alex; Fisher, Brendan; Rizzacasa, Mark A.
Abstract: The total synthesis of the biaryl ether natural product violaceic acid (1 ) in four steps is described. The steps included a SN Ar reaction between phenol7 and flouroarene12 to afford the biaryl ether13, selective reduction of a nitro group to an amine in the presence of an aldehyde, a Cu mediated Sandmeyer reaction and final hydrolysis to afford the target compound1 . The amine14 was also converted into the known iodide18 which gave impure1 on Pd mediated hydroxide cross coupling. Graphical abstract: